Test Item Quality Analysis of Final Mathematic Assessment in Islamic Elementary School - Arifatul Lutfina; Peni Susapti; Abdel Hakim Abdel Rahman (Program Studi PGMI UIN Salatiga, 2022)
This study aimed to determine the test item quality of the final mathematic assessment for the 5th-grade students of MI Muhammadiyah Kalibanger. This quantitative descriptive study applied documentation, interviews, and observation to collect the data. The data were analyzed for validity, reliability, difficulty level, differentiating power, and function. The analysis result showed that the items were categorized as good. 60% of the analyzed questions were deemed valid, and 100% of the analyzed items were reliable, with a reliability value higher than 0.40. The difficulty level was also found to be in the good category, as 56% of the total questions have a moderate difficulty level. Most questions were found to have poor differentiating power, while the questions’ function was found to be effective since 80% of the total multiple-choice questions can work properly.